Dental ceramics and the molar crown testing ground - Van P. Thompson; Dianne E. Rekow (University of São Paulo, 2004)
All ceramic crowns are highly esthetic restorations and their popularity has risen with the demand for life-like and cosmetic dentistry. Recent ceramic research has concentrated on developing a fundamental understanding of ceramic damage modes as influenced by microstructure. Dental investigations have elucidated three damage modes for ceramic layers in the 0.5-2 mm thickness using point contacts that duplicate tooth cuspal radii; classic Hertzian cone cracking, yield (pseudo-plastic behavior), and flexural cracking. Constitutive equations based upon materials properties have been developed that predict the damage modes operational for a given ceramic and thickness. Ceramic thickness or thickness of the stiff supporting core in layer crowns is critical in flexural cracking as well as the flaw state of the inner aspect of the crown. The elastic module of the supporting structure and of the luting cement and its thickness play a role in flexural fracture. Clinical studies of ceramics extending over 16 years are compared to the above relationships and predictions. Recommendations for clinical practice are made based upon the above.